FACTORS AFFECTING THE INDIAN GARMENT EXPORTERS IN LUDHIANA TO HEDGE THEIR FOREIGN EXCHANGE RISK - Girish, Jairath (2008)
In todays world of Globalization where large number of firms is entering the international markets, they are being continuously facing risk due to foreign exchange rate volatility. Consequently, they are start using hedging tools for managing foreign exchange risk. But there are still lot of firms who are not using hedging tools for some unknown reasons. This study aimed at analyzing the factors that are affecting the decision of Indian garments exporters in Ludhiana to hedge their foreign exchange risk exposure. Information has been obtained by conducting primary research on garment exporters in Ludhiana, to determine the reasons why they are using hedging tools for foreign exchange risk management. As the currency derivatives market is still at an emerging stage in India, the use of hedging instruments is a new concept for the firms, which is gaining popularity day by day. The findings show that there are lot of factors like infrastructure which are acting as an obstacle in their decision to hedge. The study also given the reasons behind each factor and how these garment exporters are reacting to it. Eventually, the paper provides a significant way for future study, which requires a quantitative analysis to be carried out on the fully disclosed data, in order to identify their outlook behind hedging activities.